2006
DOI: 10.1002/anie.200603786
|View full text |Cite
|
Sign up to set email alerts
|

A Versatile Ruthenium Catalyst for CC Bond Formation by CH Bond Activation

Abstract: Easily modified: the electronic and steric properties of a ruthenium catalyst highly active for CH bond activation (see scheme) can be modified by fine‐tuning the ligand. This makes this catalytic system very versatile as it allows functionalization of a variety of substrates. The catalyst is generated in situ from a stable and easily available ruthenium(II) source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
42
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 130 publications
(45 citation statements)
references
References 45 publications
1
42
1
1
Order By: Relevance
“…[6,7] Several conditions were examined for the reaction of these model substrates and the previously reported conditions were found to be suitable, i.e., conducting the reaction at lower temperature: 120 8C compared to 140 8C for aromatic C À H bond activation (Table 1). [5] We also found that the use of (4-CF 3 C 6 H 4 ) 3 P as ligand of the ruthenium afforded higher yields, even allowing us to run the reaction in dioxane at 100 8C. [7] Under these conditions, good yields were achieved for the functionalization of cyclic substrates with triethoxyvinylsilane ( Table 1, entries 1-4).…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…[6,7] Several conditions were examined for the reaction of these model substrates and the previously reported conditions were found to be suitable, i.e., conducting the reaction at lower temperature: 120 8C compared to 140 8C for aromatic C À H bond activation (Table 1). [5] We also found that the use of (4-CF 3 C 6 H 4 ) 3 P as ligand of the ruthenium afforded higher yields, even allowing us to run the reaction in dioxane at 100 8C. [7] Under these conditions, good yields were achieved for the functionalization of cyclic substrates with triethoxyvinylsilane ( Table 1, entries 1-4).…”
mentioning
confidence: 94%
“…We previously reported an example of the reaction of crotylamide affording allylsilane. [5] However, even if a good yield of allylsilane was achieved, the isomeric E/Z ratio was only 85:15, and we also faced reproducibility problems. During the course of our studies, we found that higher isomeric ratios were observed using (4-CF 3 C 6 H 4 ) 3 P as ligand and conducting the reaction in dioxane at lower temperature.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…In the latter case, the yield is even higher than the one that had been obtained starting directly from the corresponding acetophenone (67%). [13] The reaction course does not seem to be influenced by the electronic properties of the substituents on the aromatic ring, as carbinols bearing electron-releasing or electron-withdrawing substituents reacted equally well (entries 5-7), affording the expected alkylated ketones in 63-80% yield. Dialkylation products are generally obtained as major products because of the excess of vinylsilane and the long reaction time.…”
mentioning
confidence: 98%
“…[12,13] We wondered if this catalyst system would not only effect C À H bond activation but also alcohol oxidation via hydride transfer, as many ruthenium catalyst can do. [7] We were pleased to find that, using our previously published conditions [13] namely ruthenium trichloride as catalyst precursor, and simply by adding acetone as hydride acceptor, the reaction of 1-phenylethan-1-ol (1a) with vinyltriisopropylsilane afforded a nearly quantitative yield of ketone 3a (Table 1, entry 1). These conditions proved to be quite general as a large variety of benzyl alcohols could be easily functionalized by this tandem reaction (Table 1).…”
mentioning
confidence: 99%